2009
DOI: 10.1371/journal.pone.0008358
|View full text |Cite
|
Sign up to set email alerts
|

Adult Rat Bones Maintain Distinct Regionalized Expression of Markers Associated with Their Development

Abstract: The incidence of limb bone fracture and subsequent morbidity and mortality due to excessive bone loss is increasing in the progressively ageing populations of both men and women. In contrast to bone loss in the weight-bearing limb, bone mass in the protective skull vault is maintained. One explanation for this could be anatomically diverse bone matrix characteristics generated by heterogeneous osteoblast populations. We have tested the hypothesis that adult bones demonstrate site-specific characteristics, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
62
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 66 publications
7
62
2
1
Order By: Relevance
“…This indicates that Dlx3 regulates osteoblast differentiation in intramembranous and endochondral bones via tissue-or stage-specific molecular mechanisms. This hypothesis is further supported Appendicular skeleton and craniofacial bones display differential molecular fingerprints, 26 one notable difference being that in the appendicular skeleton skeletal patterning and osteoblastogenesis are regulated by HOX TFs, 20 whereas most of the craniofacial bones are Hox free. This Hox status would be determinant in osteogenic potential and cellular plasticity.…”
Section: Discussionmentioning
confidence: 76%
“…This indicates that Dlx3 regulates osteoblast differentiation in intramembranous and endochondral bones via tissue-or stage-specific molecular mechanisms. This hypothesis is further supported Appendicular skeleton and craniofacial bones display differential molecular fingerprints, 26 one notable difference being that in the appendicular skeleton skeletal patterning and osteoblastogenesis are regulated by HOX TFs, 20 whereas most of the craniofacial bones are Hox free. This Hox status would be determinant in osteogenic potential and cellular plasticity.…”
Section: Discussionmentioning
confidence: 76%
“…Peripheral reelin mRNA is found in various tissues and cells including the adult mammalian blood, liver, eyes, odontoblasts, osteoblasts, and osteocytes (Kobold et al, 2002;Maurin et al, 2004;Pulido et al, 2007;Smalheiser et al, 2000). The physiological significance of reelin in bone cells is unknown, but earlier studies have suggested a site-specific expression in limb and skull bones/cells and a possible link between reelin and abnormal bone remodeling in the otic capsule (Rawlinson et al, 2009;Schrauwen et al, 2009). Notably, in osteoblast-like cells, the expression of reelin can be dramatically downregulated by certain biological materials and BMP-2 (van der Zande et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in frequency, intensity and direction of such forces might lead to an imbalance of the neuromuscular stability (BudtzJörgensen, 1996;Kingsmill, 1999) and thus to an impaired activation of osteoblasts and osteoclasts, probably resulting in a discrepancy of resorption (Atwood, 1962). As recently shown by Rawlinson et al (2009) also differences in gene expression of developmentally and/or functionally distinct skeletal sites play a role in their response to mechanical stimuli. The described differences in gene expression profiles between the skull vault and limb bones were attributed to cell (osteoblast) populations of distinct embryonic lineages.…”
Section: Discussionmentioning
confidence: 99%
“…If these models also hold true for the alveolar process of the jaw and other regions of the skull remains to be investigated in more detail. Also the influence of other factors such as regionally different gene expression (long bones vs. cranial vault) resulting in site-specific osteoblast behavior, osteoclast activity and matrix composition has been discussed in this context recently (Rawlinson et al, 2009). However, loss of teeth leads invariably to atrophy of the residual alveolar ridge being irreversible, chronic, progressive and cumulative (Atwood, 1971).…”
Section: Introductionmentioning
confidence: 99%